Tuning the tilting of the spiral plane by Mn doping in YBaCuFeO5 multiferroic. (March 2021) - Zhang, Xiaodong; Romaguera, Arnau; Fabelo, Oscar; Fauth, Francois; Herrero-Martín, Javier; García-Muñoz, José Luis
Abstract: The layered perovskite YBaCuFeO5 (YBCFO) is considered one of the best candidates to high-temperature chiral multiferroics with strong magnetoelectric coupling. In RBaCuFeO5 perovskites (R: rare-earth or Y) A-site cations are fully ordered whereas their magnetic properties strongly depend on the preparation process. They exhibit partial cationic disorder at the B-site that generates a magnetic spiral stabilized through directionally assisted long range coupling between canted locally frustrated spins. Moreover the orientation of its magnetic spiral can be critical for the magnetoelectric response of this chiral magnetic oxide. We have synthesized and studied YBaCuFe1-x Mnx O5 samples doped with Mn, with the aim of increasing spin-orbit coupling effects, and found that the overall Fe/Cu cation disorder at the B-sites can be increased by doping without changing the sample preparation process. In YBaCuFe1-x Mnx O5 samples prepared under the same conditions, the T-x magnetic phase diagram have been constructed in the range 10 K-500 K combining magnetometry, X-ray and neutron powder diffraction measurements. The tilting angles of the spins in the collinear, θ col, and spiral phases, θ spiral, barely vary with temperature. In the collinear phase θ col is also independent of the Mn content. In contrast, the presence of Mn produces a progressive reorientation of the plane of the magnetic helix in the incommensurate phase, capable to transform the helicoidal spin ordering into a cycloidal one, which may critically determine the ferroelectric and magnetoelectric behavior in these compounds. Some of the observations are of interest for engineering and developing this family of potential high-temperature multiferroics. Graphical abstract: Image, graphical abstract